An analysis of forest biomass changes using geospatial tools and ground survey data: a case study in Yok Don national park, Central Highlands of Vietnam - Luong, Nguyen Viet; Tateishi, Ryutaro; Hoan, Nguyen Thanh; Tu, To Trong; Son, Le Mai (Vietnam Journal of Earth Sciences, 2014)
Vietnam conducts a national forest survey every five years using optical satellite imagery as Landsat, SPOT satellites and ground survey data. However, estimation of change in biomass due to change in forest types has not been of research interest despite of its importance in the face of climate change and applicability for REDD implementation. In this study, we used SPOT HRV satellite data of 2004, 2011 and ground survey data for analysis of changes in biomass of forest cover in Yok Don National Park, Central Highlands of Vietnam. This method has been effectively employed for mapping of land cover with overall classification accuracy of 84.30% to 86.63%. The results demonstrated that between 2004 and 2011, the biomass of Evergreen broad leaved rich forest decreased by 2.95 Megatons, biomass of the Evergreen broad leaved medium forest decreased by 0.09 Mega tons and biomass of the Dry open dipterocarps medium forest decreased 2.20 Mega tons. In that period, biomass of the Evergreen broad-leavedpoor forest increased by 0.02 Mega tons and biomass of the Dry open dipterocarps-poor forest increased by 0.91 Mega tons. References Bao Huy, 2008: Methodology for research on CO2 sequestration in natural forests to join the program of reducing emission from deforestation and degradation-REDD. Journal of Agriculture and Rural Development, MARD, 2008, pp. 1-10. Bhishma, P. et al., 2010: Forest carbon stock measurement-Guidelines for measuring carbon stocks in community-managed forest. Asia Network for Sustainable Agriculture and Bioresource (ANSAB), 79 pp. Brown, S., 1997. Estimating biomass and biomass change of tropical forests: a Primer. FAO Forestry paper–134.ISBN 92-5-103955-0. Brown, S., 2002: Measuring carbon in forests: current status and future challenges. Environmental Pollution, 116(3): 363-372.. Canh N. X. et al., 2009: Conservation planning and Sustainable Development of Yok Don National Park in 2010-2020,150pp. Chaiyo, U., Garivait, S., Wanthongchai, K., 2011: Carbon storage in Above-Ground Biomass of Tropical Deciduous Forest in Ratchaburi Province, Thailand. World Academy of Science, Engineering and Technology, pp. 636-641.. Chave, J., Andalo, C., Brown, S., Cairns, M.A. et al., 2005: Tree allometry and improved estimation of carbon stocks and balance in tropical forests. Oecologia Vol. 145, No. 1, pp. 87-99. Guide to the Kyoto Protocol to United Nations framework convention on climate change, 1998. Howarth, Wickware, 1981: Spatial analysis of land cover and land use in evaluating land degradation in Northwestern Al-Mafraq city, Jordan, pp. 55-62. IPCC, 2003: Good Practice Guidance for Land Use, Land-Use Change and Forestry. IPCC National Greenhouse Gas Inventories Programme Technical Support Unit. Printed in Japan.ISBN 4-88788-003-0.2003, 590pp. IPCC, 2006: Guidelines for National Greenhouse Gas Inventories. Volume 4: Agriculture, Forestry and Other Land Use. Chapter 4. Forest land, 83 pp. Losi, C.J. et al., 2003: Analysis of alternative methods for estimating carbon stock in young tropical plantations. Forest Ecology and Management, 184(1-3): 355-368. Lu, D. S., 2006: The potential and challenge of remote sensing-based biomass estimation. International Journal of Remote Sensing. Vol. 27, No. 7,: 1297-1328. Luong, N.V., 2011: Essay to use remote sensing images to estimate biomass as a basis for calculating the amount of CO2 sequestration by vegetation cover in in Yok Don National Park, Highlands of Viet Nam.Scientific Conference "Research, development and application of space technology-2011".ISBN: 987-604-913-032-8. Hanoi. 9pp. Ministry of Agriculture and Rural Development (MARD).Circular 34/TT-BNN issued by (MARD) of Vietnamese government, 2009: Quy định tiêu chí xác định và phân loại rừng (in Vietnamese), translated by Luong N.V-Regulation on criteria for identifying and classifying forest (in English), 5, 3. Phat, N.K. et al., 2004 : Appropriate measures for conservation of terrestrial carbon stocks- Analysis of trends of forest management in Southeast Asia. Forest Ecology and Management, 191(1-3): 283-299. Thin, N. N. et al., 2007: The vegetation of Yok Don National Park, a special ecosystem in Central Highlands of Vietnam, 2007,6, 4-5. Trung, T. V.The tropical forest ecosystem in Vietnam.Science and Technics Publishing House, Hanoi. Chapter IV, 1998, 291pp. Trung, T.V.The vegetation cover in Vietnam. Science and Technics Publishing House, Hanoi. Chapter IV, V, 1978: 276 pp. UNESCO Paris, 1973. International classification and mapping of vegetation. Published by the United Nations Educational, Scientific and Cultural Organization. ISBN 92-3-001046-4 LC No. 72-96442, 1973, 102pp. UN-REDD in Vietnam programme, 2012: Guidelines on Destructive Measurement for Forest Biomass Estimation for technical staff use. (Version for discussion). UN-REDD Vietnam Programme, 2012: Tree allometric equation development for estimation of forest above-ground biomass in Viet Nam. Part A - Introduction and Background of the Study Viet Nam.